On the Heuristic Nature of Medical Decision-Support Systems - Aliferis, C. F.; Miller, R. A. (Methods of Information in Medicine, 1995)
In the realm of medical decision-support systems, the term “heuristic systems” is often considered to be synonymous with “medical artificial intelligence systems” or with “systems employing informal model(s) of problem solving”. Such a view may be inaccurate and possibly impede the conceptual development of future systems. This article examines the nature of heuristics and the levels at which heuristic solutions are introduced during system design and implementation. The authors discuss why heuristics are ubiquitous in all medical decision-support systems operating at non-trivial domains, and propose a unifying definition of heuristics that encompasses formal and ad hoc systems. System developers should be aware of the heuristic nature of all problem solving done in complex real world domains, and characterize their own use of heuristics in describing system development and implementation.
Keywords: Heuristics; Medical Artificial Intelligence; Decision Support Systems; Problem Solving; Formal Methods; Ad hoc Methods